Industrial And Community Waste Management: Global Perspective - Godswill, Awuchi Chinaza; Gospel, Awuchi Chibueze; Otuosorochi, Amagwula Ikechukwu; Somtochukwu, Igwe Victory (American Journal of Physical Sciences, 2020)
Purpose:The review focused on the management of industrial and communal wastes. Industrial and communal waste management practices are not uniform among countries; urban and rural areas, residential, and industrial sectors, all take different approaches. Methodology: Industrial wastes can be classified on basis of their characteristics; Waste in dissolved and pollutant is in liquid form, e.g. dairy industry; Waste in solid form, but a number of pollutants within are in the liquid or fluid form, e.g. washing of minerals or crockery industry or coal. Results: Industrial waste is produced as a result of industrial activities, including materials rendered useless during manufacturing process such as that of food and chemical industries, mills, factories, and mining operations. Dirt and gravel, concrete and masonry, solvents, chemicals, scrap lumber, scrap metal, oil, etc. are types of industrial waste. Industrial or community waste may be liquid, solid, or gaseous. It may be absolutely hazardous, mirror entry, or non-hazardous waste. Hazardous waste can be toxic, ignitable, corrosive, radioactive, or reactive. Industrial waste may pollute the soil, the air, or nearby water bodies, ending up in the sea. Unique contribution to theory, practice and policy: Waste management is important component in a business' ability to maintain the ISO14001 accreditation. The ISO14001 standard encourages companies to ensure green environment and improve their environmental efficiencies every year by eliminating waste through the resource recovery practices. The principles of waste management puts some factors into consideration such as waste hierarchy, life-cycle of a product, resource efficiency, and polluter-pays principle. Common waste disposal and management methods include incineration, landfill, recycling, re-use, pyrolysis, resource recovery, composting, among others. An important method of waste management in industries and communities is the prevention of waste materials being created, better known as waste reduction. The waste management industry has adopted new technologies such as Radio Frequency Identification (RFID) tags, GPS, etc., which enable the collection of better quality data without the using estimation or manual data entry.